2017
DOI: 10.1038/s41598-017-10856-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mitochondrial Metabolic Response to Doxorubicin in Prostate Cancer Cells: An NADH, FAD and Tryptophan FLIM Assay

Abstract: Prostate cancer (PCa) is one of the leading cancers in men in the USA. Lack of experimental tools that predict therapy response is one of the limitations of current therapeutic regimens. Mitochondrial dysfunctions including defective oxidative phosphorylation (OXPHOS) in cancer inhibit apoptosis by modulating ROS production and cellular signaling. Thus, correction of mitochondrial dysfunction and induction of apoptosis are promising strategies in cancer treatment. We have used Fluorescence Lifetime Imaging Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 47 publications
6
89
0
Order By: Relevance
“…It is becoming increasingly apparent that organelles “talk” to each other to regulate key cellular functions (Murley & Nunnari, ; Quirós et al , ; Valm et al , ), but the mechanisms involved and potential roles in disease pathogenesis remain largely unexplored. Using a 2P‐FLIM assay for label‐free imaging of mitochondrial activity in live cells (Lakowicz, ; Alam et al , ; Wallrabe et al , ) (Fig A and B), we describe here a previously unknown form of inter‐organelle communication, from lysosomes to mitochondria, and reveal details of its function and mechanism of action, and how its dysregulation may represent a seminal process in AD pathogenesis and a defining molecular defect in tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…It is becoming increasingly apparent that organelles “talk” to each other to regulate key cellular functions (Murley & Nunnari, ; Quirós et al , ; Valm et al , ), but the mechanisms involved and potential roles in disease pathogenesis remain largely unexplored. Using a 2P‐FLIM assay for label‐free imaging of mitochondrial activity in live cells (Lakowicz, ; Alam et al , ; Wallrabe et al , ) (Fig A and B), we describe here a previously unknown form of inter‐organelle communication, from lysosomes to mitochondria, and reveal details of its function and mechanism of action, and how its dysregulation may represent a seminal process in AD pathogenesis and a defining molecular defect in tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 94%
“…The non-phosphorylated form of NADH acts as an electron donor in the mitochondrial electron transport chain. Typically, in cancer cells with a positive response to chemotherapy an increase of the relative contribution of protein-bound NAD(P)H and of the mean fluorescence lifetime of NAD(P)H is observed, which could be a consequence of glycolysis inhibition or the upregulation of mitochondrial respiration, or both (4,6,9). The fluorescence lifetime of NADH depends significantly on the state of the cofactor (whether "free" or "protein-bound") (3).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that fluorescence lifetime imaging (FLIM) of NAD(P)H is capable of detecting early cellular responses to anticancer treatments (4)(5)(6)(7)(8). Typically, in cancer cells with a positive response to chemotherapy an increase of the relative contribution of protein-bound NAD(P)H and of the mean fluorescence lifetime of NAD(P)H is observed, which could be a consequence of glycolysis inhibition or the upregulation of mitochondrial respiration, or both (4,6,9). The majority of these studies were carried out on in vitro models-monolayer cells or 3D tumor spheroids.…”
mentioning
confidence: 99%
“…FAD and NAD(P)H cycle from reduced to oxidized forms, thus facilitating redox reactions during energy production (e.g., oxidative phosphorylation and glycolysis). Examples of this include diagnostic imaging to reveal boundaries of demarcation between normal and cancerous tissues or measurement of optical redox ratios (29,32,(34)(35)(36)(37)(38)(39)(40)(41). The signals that result vary depending on the NAD(P)H reduced or oxidized form (20,22), location inside of the cell (e.g., mitochondria, cytosol) (23), and binding status with enzymes (e.g., malate, lactate, isocitrate, and succinate dehydrogenases) (24,25).…”
mentioning
confidence: 99%
“…Yet for many studies, the bound enzyme might depend on the variation in the metabolism and is of lesser importance compared to the purpose for detecting changes in the NAD(P)H autofluorescence. Examples of this include diagnostic imaging to reveal boundaries of demarcation between normal and cancerous tissues or measurement of optical redox ratios (29,32,(34)(35)(36)(37)(38)(39)(40)(41).…”
mentioning
confidence: 99%